Manajemen Pembelajaran Pendidikan Agama Islam dalam Meningkatkan Efektivitas Pembelajaran di Sekolah - Shalahuddin Shalahuddin; Rahmi Apriani; Muhammad Jibril; Al Bima (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Increasing competition among Islamic secondary education institutions requires madrasah to implement effective and sustainable educational promotion strategies. This study aims to analyze educational promotion strategies at MAS Nahdatul Islam Mandau through the integration of the 7P service marketing mix and digital promotion approaches. Employing a qualitative case study design, the research was conducted at MAS Nahdatul Islam Mandau, Bengkalis Regency, Riau. Data were collected through in-depth interviews, participant observation, and document analysis involving the head of the madrasah, the student admission committee, and parents of prospective students. Data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that educational promotion strategies were implemented through four main promotional forms: personal selling, mass selling, sales promotion, and word of mouth. Personal selling, particularly through Road to School activities, emerged as the most effective strategy in building trust and increasing enrollment interest. Digital promotion via social media functioned as a supporting tool to enhance institutional visibility, although its impact remained limited due to contextual characteristics of rural communities. Supporting factors included a strategic location, affordable tuition fees, religious-based programs, and social media utilization, while inhibiting factors encompassed limited facilities, intense competition, and public perceptions regarding private education costs. This study contributes to Islamic education marketing literature by highlighting the importance of integrating the 7P marketing mix with relational and context-sensitive promotion strategies. Practically, the findings offer strategic insights for madrasah administrators in designing adaptive and community-oriented promotion models in competitive educational environments